Rehabilitation, Redistribution or Dissipation: The Evidence for Choosing Among Bankruptcy Hypotheses - James W. Bowers (Washington University Law Quarterly, 1994)
This Article addresses that new redistributive view of bankruptcy in its two most typical versions-which I denominate the "Rehabilitative" and "Pure Redistribution" hypotheses, respectively-and argues that neither is consistent with the existing empirical data concerning corporate reorganizations. It then proposes a new thesis about bankruptcy which is inspired not only by the existing data, but also by new theoretical insights: that measures which avoid some kinds of market failures, such as externalities, entail their own kinds of costs, e.g., by fostering holdout behavior. The new thesis-that bankruptcy law tends to waste resources- I denominate the "Dissipative" thesis.
Keywords: Bankruptcy law; United States; Bankruptcy reorganization